In-between spaces what motivates young Filipino adults in binge-watching anime on streaming services - Guariña, Anton Miguel P.
This study aims to identify and explore the various factors that influence the motives and gratification-seeking behavior of audiences who engage in anime as their choice of media to binge-watch as it seeks to understand how audiences situate it as a practice within their lifestyles, The study will employ the Uses and Gratification theory as articulated by (Katz, E., Blumer, J. & Gurevitch, M., 1974) to describe how participants navigate through the practice as a gratification-seeking audience, along with their diverse motivations and the personalization of media. Additionally, it will incorporate Husserl's theory (1931) on phenomenology to investigate the lived experiences of the participants.